2022
DOI: 10.1186/s43163-022-00315-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude, and practice of ear care among Jazan general population, Saudi Arabia

Abstract: Objective The present study aimed at determining the knowledge, attitude, and practice of ear care among Jazan population and its association with sociodemographic variables. Methods This is a cross-sectional study conducted between January and June 2022 in the Jazan region, Saudi Arabia. Data was collected using an Arabic electronically questionnaire and analyzed using SPSS software version 23. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…A study conducted in Majmaa, Saudi Arabia, documented that 55.4% of the university students showed poor knowledge about the practices of self-ear cleaning (6). Contradicting this report, a study conducted in Jazan, Saudi Arabia, revealed that there were good knowledge (91.9%), attitude (90.4%), and practices (83.9%) among the general population toward self-ear cleaning [ 17 ]. Among the determinant of knowledge, 54% of their subjects do not believe that ear wax should be removed continuously, and neither their population had the habit of ear cleaning with sharp objects such as pencils, pins, and earbuds (81.6%) nor use of oil in ears (94.4%).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Majmaa, Saudi Arabia, documented that 55.4% of the university students showed poor knowledge about the practices of self-ear cleaning (6). Contradicting this report, a study conducted in Jazan, Saudi Arabia, revealed that there were good knowledge (91.9%), attitude (90.4%), and practices (83.9%) among the general population toward self-ear cleaning [ 17 ]. Among the determinant of knowledge, 54% of their subjects do not believe that ear wax should be removed continuously, and neither their population had the habit of ear cleaning with sharp objects such as pencils, pins, and earbuds (81.6%) nor use of oil in ears (94.4%).…”
Section: Discussionmentioning
confidence: 99%